Evaluation of Video-Based Instructional Coaching for Middle School Teachers: Evidence from a Multiple Baseline Study. Issue 4 (2nd October 2018) - Knight, David; Hock, Michael; Skrtic, Thomas M.; Bradley, Barbara A.; Knight, Jim
Abstract: We designed a multiple baseline study to evaluate an instructional coaching model in which coaches use video recordings of collaborating teachers' classrooms to inform their coaching practices. In this model, teachers and coaches use video evidence to co-construct a student-based goal and identify best practices to reach their goal. We found that the instructional coaching model is associated with greater use of effective pedagogical strategies among teachers and increased student engagement in the classroom.